IMPLEMENTATION OF THE WASTE BANK PROGRAM IN HANDLING WASTE IN THE CITY OF SERANG - Nisa, Zahra Khoiru; Agusti, Indah Dewi; Winarti, Aas; Apriliansyah, Irgi; Zaty, Fathur Perdana (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2024)
Waste management in Serang City remains a significant challenge for the local government. With a population of 735,651 in 2023 and a density of 2,700 people/km², the volume of waste produced continues to increase. To address this, the Serang City Government has implemented a waste bank program aimed at reducing the amount of waste ending up in the Final Processing Site (TPA). This program seeks to raise public awareness about waste management through sorting, recycling, and utilizing waste. This study employs a qualitative approach to examine the implementation of the waste bank program in Serang City. Smith's model is utilized to analyze the policy implementation process, focusing on four variables: idealized policy, target groups, implementing organization, and environmental factors. The findings indicate that, despite the efforts of the Environmental Agency and waste bank organizations, the program's implementation has not been optimal. Contributing factors include a lack of community participation, an insufficient number of personnel, and inadequate facility support. However, some sub-districts exhibit high levels of community participation, with residents utilizing waste banks as a source of economic value. This demonstrates the potential for the program to succeed if these issues are addressed. Recommendations for improving the waste bank program include enhancing community engagement through education and outreach, increasing the number of personnel dedicated to the program, and providing better facilities and resources to support waste management efforts. By addressing these challenges, the Serang City Government can make significant strides in improving waste management and reducing the environmental impact of waste.